THE USE OF PICTURE AS MEDIA TO IMPROVE STUDENTS' READING COMPREHENSION - Aldi Maitulung Bander; Ignatius J. C. Tuerah; Sanerita T. Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to determine whether or not the use of pictures and other media can increase students' reading comprehension. The study used a one group pre-test and post-test pre-experimental design. Twenty students served as the study's subject, and the research was carried out at SMP Negeri 2 Tondano. The writer employed tests with multiple choices and a completion of 10 numbers for each test in order to acquire the data. Prior to treatment, the students took a pre-test; following treatment, they took a post-test. The pre-test had an average score of 58.75 and a standard deviation of 6.68. The mean post-test score was 84.75, and the standard deviation was 6.0 1. One could argue that the post-test outcome was better than the pre-test. Thus it could be concluded that the use of pictures as media can improve students reading comprehension.